(untitled) (The International Journal for Scientific Research, 2025)
This study investigated the effects of tamarind seed kernel powder (TKP) incorporation (0–20%) on the rheological and quality properties of dough and bread produced from two wheat flour types: local flour (Alsayed Flour Mills) and imported Egyptian flour (Salara). Significant improvements in water absorption, dough development time, and stability were observed with increasing TKP levels, with more pronounced effects in the local flour. Water absorption increased to 66.5% (local) and 61.5% (imported) at 20% TKP, reflecting the superior protein strength and water-binding capacity of the local flour. Dough development time rose from 1.7 to 11.5 minutes (local) and from 1.4 to 5.7 minutes (imported), while stability reached 8.7 and 6.7 minutes, respectively. The gluten index was higher in local flour (135.64) than in imported flour (93.66), though both decreased with TKP addition due to gluten dilution. Proximate analysis revealed increased protein (up to 13.51%), fiber (0.7% to 1.44%), and ash content with TKP enrichment, alongside reduced carbohydrate levels. Sensory evaluation indicated that higher TKP levels negatively affected color, aroma, taste, and texture, with overall acceptability scores declining to 5.26 (local) and 5.33 (imported) at 20% TKP. The local flour demonstrated superior gluten strength and nutritional enhancement potential.